Gut Microbes in Immunoglobulin A Nephropathy and Their Potential Therapeutic Applications - Wang, Yi; Tian, Lingling; Sun, Lin; Zhou, Wenjing; Zhi, Wenqiang; Qing, Jianbo; Abdi Saed, Yasin; Dong, Lina; Zhang, Xiadong; Li, Yafeng (Frontiers in Medicine, 2022)
Microbial ecosystem consists of a complex community of bacterial interactions. Because the interaction between gut microbiota and host involves many diseases and seriously affects human health, the study of the interaction mechanism between gut microbiota and host has attracted great attention. The gut microbiome is made up of 100 trillion bacteria that have both beneficial and adverse effects on human health. The development of IgA Nephropathy results in changes in the intestinal microbial ecosystem that affect host physiology and health. Similarly, changes in intestinal microbiota also affect the development of IgA Nephropathy. Thus, the gut microbiome represents a novel therapeutic target for improving the outcome of IgA Nephropathy, including hematuria symptoms and disease progression. In this review, we summarize the effect of intestinal microbiota on IgA Nephropathy in recent years and it has been clarified that the intestinal microbiota has a great influence on the pathogenesis and treatment of IgA Nephropathy. A large number of studies have shown that intestinal microbes play a vital role in the treatment of kidney disease.